2006
DOI: 10.1128/jvi.02381-05
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Virus Evades Innate and Adaptive Immunity via the NS1 Protein

Abstract: Both antibodies and T cells contribute to immunity against influenza virus infection. However

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
293
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 265 publications
(300 citation statements)
references
References 50 publications
7
293
0
Order By: Relevance
“…In 2007, Pauli et al (2008) reported that IAVs suppress type I IFN signalling by upregulating the suppressor of cytokine signalling-3 (SOCS-3) protein, which is a potent endogenous inhibitor of JAK/STAT signalling (Pauli et al, 2008). In addition to inhibiting innate immunity by preventing type I IFN release, IAVs attenuate adaptive immunity by inhibiting the maturation of human dendritic cells and the capacity of dendritic cells to activate T-cell responses (Fernandez-Sesma et al, 2006). In addition to the blockade of innate and adaptive immunity, Krug et al (2003) found that the NS1 proteins from A/Tx/36/91 suppressed host gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, Pauli et al (2008) reported that IAVs suppress type I IFN signalling by upregulating the suppressor of cytokine signalling-3 (SOCS-3) protein, which is a potent endogenous inhibitor of JAK/STAT signalling (Pauli et al, 2008). In addition to inhibiting innate immunity by preventing type I IFN release, IAVs attenuate adaptive immunity by inhibiting the maturation of human dendritic cells and the capacity of dendritic cells to activate T-cell responses (Fernandez-Sesma et al, 2006). In addition to the blockade of innate and adaptive immunity, Krug et al (2003) found that the NS1 proteins from A/Tx/36/91 suppressed host gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, NS1 has been shown to limit the induction of numerous specific transcriptional events associated with the maturation of human dendritic cells (DCs) in response to virus infection (38). In particular, expression of IL-12 p35 (a subunit of the proinflammatory and immunoregulatory cytokine IL-12) was found to be inhibited in DCs infected with recombinant viruses expressing NS1 (38).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, expression of IL-12 p35 (a subunit of the proinflammatory and immunoregulatory cytokine IL-12) was found to be inhibited in DCs infected with recombinant viruses expressing NS1 (38). IL-12 is a key regulator of host innate and adaptive immune responses during infection: it enhances the cytolytic activity of natural killer (NK) cells and CD8 ϩ T cells, and contributes to the optimal production of IFN-␥ (39).…”
Section: Discussionmentioning
confidence: 99%
“…The NS1 protein of influenza virus and the V protein of SeV inhibit the induction of type I IFNs by blocking intracellular dsRNA signaling (20,(31)(32)(33)(34). The influenza virus NS1 protein has also been shown to inhibit viral induction of DC maturation (5,35). Thus, we hypothesized that SeV-C may encode an impaired type I IFN antagonist allowing stronger DC stimulation by viral dsRNA than SeV-52.…”
Section: Strong DC Maturation By Sev-c Is Not Antagonized By a Sev Wimentioning
confidence: 99%